1983
DOI: 10.1530/acta.0.1020625
|View full text |Cite
|
Sign up to set email alerts
|

Reversible inhibition of sperm production and gonadotrophin secretion in men following combined oral medroxyprogesterone acetate and percutaneous testosterone treatment

Abstract: Abstract. Six men requesting male contraception received a daily oral dose of 20 mg medroxyprogesterone acetate (MPA) in combination with 50 or 100 mg percutaneous testosterone for 1 year. From the third month the sperm concentration was < 106/ml for all the men at one time or another during treatment, and usually < 5 × 106/ml, with an average reduction of 95% with respect to pre-treatment values. The sperm count returned to previous values 3–6 months after cessation of the treatment. While FSH and LH se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
1
3

Year Published

1984
1984
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 0 publications
0
19
1
3
Order By: Relevance
“…In the corpus epididymidis of the bull the reduction in spermatogenesis is accompanied by a 50% diminution in proteins and a 75% reduction in glycerophosphocholine (Gustafsson, 1966). In man, inhibition of sperm production by a combination of medroxyprogesterone acetate + testosterone leads to oligozoospermia, then azoospermia with a concomitant reduction in seminal carnitine (Soufir et al, 1983). These results seem to indicate that the presence of spermatozoa in the epididymis stimulates the production of certain components in the fluid and that this is relative to the number of spermatozoa.…”
Section: Discussionmentioning
confidence: 89%
“…In the corpus epididymidis of the bull the reduction in spermatogenesis is accompanied by a 50% diminution in proteins and a 75% reduction in glycerophosphocholine (Gustafsson, 1966). In man, inhibition of sperm production by a combination of medroxyprogesterone acetate + testosterone leads to oligozoospermia, then azoospermia with a concomitant reduction in seminal carnitine (Soufir et al, 1983). These results seem to indicate that the presence of spermatozoa in the epididymis stimulates the production of certain components in the fluid and that this is relative to the number of spermatozoa.…”
Section: Discussionmentioning
confidence: 89%
“…Scrotal and nonscrotal patches, testosterone gel and DHT gel and, as mentioned above, also orally effective testosterone undecanoate maintain physiological testosterone concentrations and are well tolerated [14][15][16] . Unfortunately these androgen preparations either alone 10 or in combination with different progestins show generally disappointing spermatogenic suppression [17][18][19][20][21][22] . Compared to the results of studies in which the same progestins were added to testosterone enanthate, the latter showed much better efficacy 21,[23][24][25] .…”
Section: T E S T O S T E R O N E a L O N Ementioning
confidence: 99%
“…Deux équipes françaises [5,9] ont utilisé le MPA par voie orale (20 mg par jour) et associé, pour les premiers, à 100 ou 50 mg par jour de testosté rone par voie percutanée (percutacrine androgénique) et à 125 mg de DHT ou de testostérone en gel pour la deuxième équipe. Dans les deux cas, les dosages hormonaux permettent au même titre que les spermogrammes de vérifier l'effet de la thérapeutique et éventuellement de la modifier.…”
unclassified
“…Toutefois, sur 22 éjaculats obtenus après le 3e mois, 2 seule ment dépassaient 5 millions de spermatozoïdes par millilitre [9], Néan moins, Guérin et al [5] remarquent que chez 1 de leurs patients le nombre de spermatozoïdes s'est progressivement élevé après 6 mois, ce qui consti tue un très sérieux handicap pour cette méthode. Soufiret al [9] ont, quant à eux, noté une discrète élévation de la glycémie qui demeurait néanmoins dans des limites physiologiques.…”
unclassified
See 1 more Smart Citation